Analisis Strategi Komunikasi Dalam Pelaksanaan Pelatihan Penggunaan Aplikasi Grab Merchant Pada Pt. Grab Teknologi Indonesia - Wulantresna, Pratami; Pramesti Dewi, Rd. Dancu Lokita; Prihadini, Diana; Retnosari, Desi (LUGAS Jurnal Komunikasi, 2022)
In  communicating  the  right  strategy  is  needed  so  that  the  purposeof  communication  can  be  achieved  well.  Communication  is  donewithout  the  resulting  strategy  many  errors  in  the  actualization  ofthe  information  obtained.  Strategy  communication  is  not  only  theformulation  of  concepts  and  implementation,  more  than  thatstrategy communication is carried out in stages with a clear goal.  There  are  6  stages  communication  strategy  is  the  source,message,  channel,  receiver,  effect  and  feedback.  As  An  AnalysisOf  Communication Strategies In The Implementation Of Training  Use  of  Grab  Merchant  application  at  PT.  GrabTechnology  Indonesia.  Is  a  training  program,  the  training  needsto  pay  attention to  management  or  management.  Management  is  important  so  thattraining  objectives  can  be  achieved  to  the  maximum.  As  withmanagement  in general, management  training programs related  tothe  activities  of  the  Trident,  namely  planning,  implementation,  andevaluation.